Combined replantation of the posterior arch of the atlas and bilateral axial lamina in the treatment of intradural schwannoma: a case report - Leng, Ao; Li, Jiacheng; Meng, Lingzhi; Wang, Qi (Frontiers in Surgery, 2024)
Background: Laminotomy and laminar replantation have emerged as novel treatment modalities for intraspinal tumors, aiming to minimize postoperative complications and retain spinal mobility. However, existing research predominantly emphasizes their application in the thoracolumbar spine. The unique anatomy of the atlantoaxial segments necessitates surgical techniques that differ from those used in other spinal regions, and the clinical effect of such procedure remains unknown.Case presentation: A 61-year-old male patient with intradural schwannoma at the atlantoaxial level was operated on. The patient underwent posterior laminectomy, as well as a combined replantation of the posterior arch of the atlas and bilateral axial laminae. Postoperatively, the patient experienced significant neurological improvement, with no deformities or instability on the radiological assessments during the follow-up.Laminotomy with combined replantation of the posterior arch of the atlas and bilateral axial lamina emerges as an effective approach for managing intraspinal tumors at the atlantoaxial level. This technique not only offers ample operating space but also restores the stability of the spinal canal. Moreover, it preserves the mobility of the atlantoaxial segment, minimizes impact on adjacent segments, and mitigates the formation of postoperative fibrosis.